PERAN ORANG TUA DALAM MEMOTIVASI BELAJAR SISWA DI MADRASAH IBTIDAIYAH HIDAYATUL MUBTADIIN TASIKMADU KECAMATAN LOWOKWARU KOTA MALANG - Athifatun Nabila; Ika Ratih Sulistiani; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
The role is the participation of parents in the education process of children by devoting all thoughts and attention to children so that children feel more enthusiastic in their learning. Learning is a mental or psychological activity that occurs in active interactions with the environment, which results in changes in knowledge, understanding, skills and attitude values. Success in the teaching and learning process can be affected by motivation from within students. Motivation can lead to interest in learning that will focus and maximize student learning. By building intrinsic motivation, it is better than building extrinsic motivation. Because by using intrinsic motivation, students will begin to learn slowly with their sincerity. However, with the existence of extrinsic motivation will determine student interest in learning, when within students there has been a desire to learn, but extrinsic factors do not support, then students will lose enthusiasm in terms of learning. Motivation is the drive that causes one's actions. Motivation has an important role in the learning effort. Learning motivation has three functions, as follows: (1) as a reference for carrying out activities in achieving goals (2) encouraging students to obey, and (3) encouraging students' desire to do more activities in order to find maximum results. affect the success of the learning process. The success of students is certainly from the support and guidance of parents. Therefore, every parent must motivate their children to learn to be parents who are role models for children, so that children become good and educated individuals. Key word: role of parents, motivation, student